VO#044 The quotation for RCC bench & floor joints at stair rev.01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the revised quotation for RCC bench & floor joints at stair of BRACU new campus project.